Functional consequences of a polymorphism affecting NF-kappaB p50-p50 binding to the TNF promoter region. - Udalova, I; Richardson, A; Denys, A; Smith, C; Ackerman, H; Foxwell, B; Kwiatkowski, D (2000)
Stimulation of the NF-kappaB pathway often causes p65-p50 and p50-p50 dimers to be simultaneously present in the cell nucleus. A natural polymorphism at nucleotide -863 in the human TNF promoter (encoding tumor necrosis factor [TNF]) region provides an opportunity to dissect the functional interaction of p65-p50 and p50-p50 at a single NF-kappaB binding site. We found that this site normally binds both p65-p50 and p50-p50, but a single base change specifically inhibits p50-p50 binding. Reporter gene analysis in COS-7 cells expressing both p65-p50 and p50-p50 shows that the ability to bind p50-p50 reduces the enhancer effect of this NF-kappaB site. Using an adenoviral reporter assay, we found that the variant which binds p50-p50 results in a reduction of lipopolysaccharide-inducible gene expression in primary human monocytes. This finding adds to a growing body of experimental evidence that p50-p50 can inhibit the transactivating effects of p65-p50 and illustrates the potential for genetic modulation of inflammatory gene regulation in humans by subtle nucleotide changes that alter the relative binding affinities of different forms of the NF-kappaB complex.